Features of jihadist education in the verses of The Battle of Uhud in Surat Al-Imran - Nakouh, AbdAlhamid Hassan (Journal of Educational and Psychological Sciences, 2023)
This research aims to derive the features of jihadist education in the verses of the Battle of Uhud in Surat Al-Imran, following the deductive approach, and has reached the following results: The educational features derived from the verses of the Battle of Uhud in Surat Al-Imran: Commitment to piety in word and deed, response to the command of God Almighty, submission to the command of God Almighty, good trust in God Almighty, patience, remembrance of God’s graces and His provision and grace upon the believers, obedience, spending, keenness on Familiarity and reconciling oneself, encouragement to acquire the qualities of the believers mentioned in the two Surahs, evoking God’s presence with His servants, pardon and benevolence and restraining anger, investigation of what is permissible and forbidden, encouragement and consolation after joy, comprehension of the rule of soreness: (affliction, deliberation of days, adoption of martyrs, scrutiny of believers by expiating sins and raise scores, matching words to deeds). Awareness of the reality of death, following the example of the righteous predecessors, adhering to the characteristics of the divine leader (investigating what is permissible and forbidden, not being harsh, leaving the hardness of the heart, pardoning, seeking forgiveness for those who are in charge of their affairs, consultation, determination, trust in God Almighty) and among his duties as well is inspecting the army and lowering the status of the one who has the status. realization Causes and rule of calamity. Consoling the believers and entertaining them, transcendence in the religion of God Almighty without weakness or sadness, investigating what is permissible and forbidden, mentioning the divine in word and deed, taking precedence in the doors of goodness, martyrdom, seeking good news with what God Almighty has, returning after calamity.